2018
DOI: 10.1128/msphere.00401-17
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Change in the Marburg Virus Glycoprotein Arises during Serial Cell Culture Passages and Attenuates the Virus in a Macaque Model of Disease

Abstract: Marburg virus (MARV) causes disease with high case fatality rates, and there are no approved vaccines or therapies. Licensing of MARV countermeasures will likely require approval via the FDA's Animal Efficacy Rule, which requires wellcharacterized animal models that recapitulate human disease. This includes selection of the virus used for exposure and ensuring that it retains the properties of the original isolate. The consequences of amplification of MARV for challenge studies are unknown. Here, we serially p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(56 reference statements)
2
15
0
Order By: Relevance
“…The methylcellulose and crystal violet assay was used to determine the titer of the NHP exposure dose for the 8U EBOV dose study (as previously described in [ 15 ]), while the agarose and neutral red assay was used for all other viral titrations. As expected, all of the virus exposure doses were below the assay limit of detection, consistent with previous work showing that some particles do not yield plaques in cell culture, but that they can nonetheless cause lethal disease in NHPs [ 15 , 16 ]. When the exposure doses were prepared, calculations were performed using viral titers determined previously (approximately one year prior to the animal exposures for all stocks except the 8U EBOV).…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…The methylcellulose and crystal violet assay was used to determine the titer of the NHP exposure dose for the 8U EBOV dose study (as previously described in [ 15 ]), while the agarose and neutral red assay was used for all other viral titrations. As expected, all of the virus exposure doses were below the assay limit of detection, consistent with previous work showing that some particles do not yield plaques in cell culture, but that they can nonetheless cause lethal disease in NHPs [ 15 , 16 ]. When the exposure doses were prepared, calculations were performed using viral titers determined previously (approximately one year prior to the animal exposures for all stocks except the 8U EBOV).…”
Section: Methodssupporting
confidence: 90%
“…Nonhuman primates were observed at least twice daily for up to 21 days post-exposure, at which time any survivors were euthanized. Clinical scores were reported to the responsible veterinarian, and euthanasia was approved when scores indicated that an NHP was terminally ill. A brief description of the clinical scoring system (described previously in [ 16 ]) is as follows. Animals received one point each for reductions in feed or fluid intake, dehydration, no stool production, rough hair coat, nasal discharge, or bleeding at the blood collection site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly, these FMD vaccines are produced by propagation of FMDV in BHK-21 cells [7]. It is known for many viruses, however, that cultivation outside the natural host, for instance during the course of adaptation to a permanent cell line, can result in alterations to the amino acid sequence of viral proteins [9][10][11][12][13]. Especially RNA viruses, such as FMDV, consist of viral populations without a defined genomic sequence but of distributions of related but non-identical genomes (quasispecies).…”
Section: Introductionmentioning
confidence: 99%